Parkin is a disease modifier in the mutant SOD1 mouse model of ALS. Issue 10 (20th August 2018) - Palomo, Gloria M; Granatiero, Veronica; Kawamata, Hibiki; Konrad, Csaba; Kim, Michelle; Arreguin, Andrea J; Zhao, Dazhi; Milner, Teresa A; Manfredi, Giovanni
Abstract: Mutant Cu/Zn superoxide dismutase (SOD1) causes mitochondrial alterations that contribute to motor neuron demise in amyotrophic lateral sclerosis (ALS). When mitochondria are damaged, cells activate mitochondria quality control (MQC) mechanisms leading to mitophagy. Here, we show that in the spinal cord of G93A mutant SOD1 transgenic mice (SOD1‐G93A mice), the autophagy receptor p62 is recruited to mitochondria and mitophagy is activated. Furthermore, the mitochondrial ubiquitin ligase Parkin and mitochondrial dynamics proteins, such as Miro1, and Mfn2, which are ubiquitinated by Parkin, and the mitochondrial biogenesis regulator PGC1α are depleted. Unexpectedly, Parkin genetic ablation delays disease progression and prolongs survival in SOD1‐G93A mice, as it slows down motor neuron loss and muscle denervation and attenuates the depletion of mitochondrial dynamics proteins and PGC1α. Our results indicate that Parkin is a disease modifier in ALS, because chronic Parkin‐mediated MQC activation depletes mitochondrial dynamics‐related proteins, inhibits mitochondrial biogenesis, and worsens mitochondrial dysfunction. Synopsis: Accumulation of misfolded proteins linked to ALS leads to mitochondrial damage. This triggers mitochondrial quality control mechanisms, which eliminate damaged mitochondria through mitophagy. However, chronically enhanced mitophagy becomes maladaptive, leading to mitochondrial loss. Mitochondria in the spinal cord of SOD1 mutant mice are marked for protein degradation and mitophagy. Parkin tags damaged mitochondria in the spinal cord of SOD1 mutant mice and is increasingly turned over, as disease progresses. Increased activation of Parkin‐mediated mitochondrial quality control causes mitochondrial depletion in SOD1 mutant spinal cord. Parkin induces the degradation of Miro1 and other key proteins related to mitochondrial dynamics in SOD1 mutant spinal cord. Genetic ablation of Parkin in SOD1 mutant mice attenuates mitochondrial depletion and delays disease progression. Abstract : Accumulation of misfolded proteins linked to ALS leads to mitochondrial damage. This triggers mitochondrial quality control mechanisms, which eliminate damaged mitochondria through mitophagy. However, chronically enhanced mitophagy becomes maladaptive, leading to mitochondrial loss.